2017
DOI: 10.1001/jamapediatrics.2017.0091
|View full text |Cite
|
Sign up to set email alerts
|

Home-Based Hypnotherapy Self-exercises vs Individual Hypnotherapy With a Therapist for Treatment of Pediatric Irritable Bowel Syndrome, Functional Abdominal Pain, or Functional Abdominal Pain Syndrome

Abstract: Individual gut-directed hypnotherapy (HT) is effective in pediatric irritable bowel syndrome (IBS) and functional abdominal pain or functional abdominal pain syndrome (FAP[S]). It is, however, unavailable to many children.OBJECTIVE To compare the effectiveness of HT by means of home-based self-exercises using a CD with that of individual HT (iHT) performed by qualified therapists. DESIGN, SETTING, AND PARTICIPANTSThis noninferiority randomized clinical trial with a follow-up of 1 year after the end of treatmen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
120
0
5

Year Published

2017
2017
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 81 publications
(127 citation statements)
references
References 34 publications
2
120
0
5
Order By: Relevance
“…Previous studies have demonstrated the effectiveness of HT in children with functional abdominal complaints and irritable bowel syndrome, with adequate relief in more than 80% of the children at 1-year follow-up [27, 34]. The relatively high treatment success of HT in children with abdominal pain, compared to the results in this study in children with primary headache, may possibly be explained by different characteristics of these two types of chronic pain.…”
Section: Discussionmentioning
confidence: 46%
See 1 more Smart Citation
“…Previous studies have demonstrated the effectiveness of HT in children with functional abdominal complaints and irritable bowel syndrome, with adequate relief in more than 80% of the children at 1-year follow-up [27, 34]. The relatively high treatment success of HT in children with abdominal pain, compared to the results in this study in children with primary headache, may possibly be explained by different characteristics of these two types of chronic pain.…”
Section: Discussionmentioning
confidence: 46%
“…However, no study has specifically investigated the effect of TM on headache in paediatric patients. It has been reported that hypnotherapy is also an effective method for reduction of chronic pain, stress and anxiety [10, 19, 27, 28]. One observational study reported that HT in children may positively contribute to the reduction of headache complaints, with a lasting effect, but good randomised clinical trials (RCTs) are lacking [14].…”
Section: Introductionmentioning
confidence: 99%
“…Diese variieren teilweise zwischen fünf und 12 Sitzungen und einer Dauer von einer halben bis ganzen Stunde [97]. Allerdings zeigte eine aktuelle Studie bei Kindern mit RDS-Symptomatik die Nichtunterlegenheit einer CD vermittelten Hypnotherapie im Vergleich zur Hypnotherapie im therapeutischen Einzelsetting [99], sodass diese Therapie auch ressourcensparend angeboten werden könnte.…”
Section: Hypnotherapieunclassified
“…To overcome this problem, researchers experimented with alternative forms of delivering treatment such as homebased hypnotherapy. Rutten et al have shown that home-based therapy using audio CDs was not inferior to treatments by a hypnotherapist 43 . A systematic review comparing hypnotherapy performed by a therapist with studies that used self-exercises on an audio CD concluded that any form of hypnotherapy is beneficial to improve abdominal pain in children 1 .…”
Section: Hypnosismentioning
confidence: 99%